STANDALONE GENERAL PURPOSE DATA LOGGER DESIGN AND IMPLEMENTATION (Nigerian Journal of Technology, 2015)
This paper describes the design of a general purpose data logger that is compatible with a variety of transducers, potentially permitting the measurement and recording of a wide range of phenomena. The recorded data can be retrieved to a PC via an RS-232 serial port. The standalone general purpose data logger centered on a single microcontroller unit (MCU) the PIC18F4520. The circuit takes an input range of 15 – 30V DC in addition; an in-built 9V rechargeable battery provides backup power in the absence of an external source.  The microcontroller input form the Transduceroutput was conditioned within the allowable voltage range, the ADC calculates a binary value that is equivalent to its input (analog) voltage.  The in-built 10-bit ADC of the PIC18F4520 converts the analog input to a digital output by successive approximation, the 8 MSBs of the ADC are stored whereas the 2 LSBs are discarded which makes the output of the ADC varies from 0 to 255. Although the PIC18F4520 features 256 bytes of non-volatile EEPROM data memory, four AT24C256 2-wire serial EEPROM chips were used for data storage. The four chips were cascaded to form a memory bank that connects to the MCU via a common single 2-wire bus.The hardware employed to achieve the RS-232 serial interface was a 9-pin D-shell serial connector and a voltage level translator chip (Maxim’s MAX232). The connector simply allows the device to be coupled to a serial port of a PC using a standard serial cable. The TIMER1 module of the PIC18F4520 was configured such that its 16-bit register is incremented on the rising edge of the external clock signal applied to its input pin (pin 16). The input pins of the MCU that are dedicated to the switches are pulled up by resistors R11, R12, R13, R14, R15 and R16.  The push buttons temporarily pull down the input signal when depressed. The output devices consist of a “Liquid Crystal Display” (LCD) device, four general purpose LEDs, and a buzzer. The LCD displays the momentary status of the data-logger in terms of date, time, sampling rate and nature of logged data.  The LEDs are used to display the four MSBs of the measured data and the buzzer is used to raise an alarm if and when necessary but may be disabled in hardware by opening jumper J4. The design was implemented and simulated on Labcenterproteus and the components were mounted on a double layered PCB (Printed Circuit Board) that provides the tracks that make up the circuit.The prototype design realized was found to work satisfactorily. http://dx.doi.org/10.4314/njt.v34i2.18